2020
DOI: 10.1002/jper.20-0481
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjunctive procedures on recombinant human fibroblast growth factor‐2–mediated periodontal regeneration therapy: A retrospective study

Abstract: Background: Human fibroblast growth factor-2 (rhFGF-2) therapy has been used for periodontal tissue regeneration. However, few studies have reported their adjunctive procedures based on strategy of tissue engineering. The aim of this retrospective study is to assess the adjunctive effects of modified papilla preservation technique (mPPT) and combination with autogenous bone grafts (AG) on the rhFGF-2 therapy. Methods: Total of 44 sites underwent rhFGF-2 therapies and the evaluations in the survey periods. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Although MMP8 and MMP3 and IL-1β are important inducers of inflammation in our hyperglycemic coculture model, the multi-omics data integration model showed that FGF2, GM-CFS and IL-10 are key pro-inflammatory cytokines that play a major role in periodontitis-induced inflammatory response in a hyperglycemic microenvironment. FGF2 and IL-10 are known to enhance periodontal tissue regeneration [31] and to decrease gingival inflammation [32], respectively. Their highlighted role during periodontitis-induced inflammation may suggest that they are secreted by the coculture model to counteract pro-inflammatory cytokines and matrix metalloprotease secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Although MMP8 and MMP3 and IL-1β are important inducers of inflammation in our hyperglycemic coculture model, the multi-omics data integration model showed that FGF2, GM-CFS and IL-10 are key pro-inflammatory cytokines that play a major role in periodontitis-induced inflammatory response in a hyperglycemic microenvironment. FGF2 and IL-10 are known to enhance periodontal tissue regeneration [31] and to decrease gingival inflammation [32], respectively. Their highlighted role during periodontitis-induced inflammation may suggest that they are secreted by the coculture model to counteract pro-inflammatory cytokines and matrix metalloprotease secretion.…”
Section: Discussionmentioning
confidence: 99%
“…who is a board-certified doctor (BD) from the Japanese Society of Periodontology. Therefore, calibration was not carried out same as in a previous study [ 35 ]. CAL was calculated based on PD, gingival recession (GE), PESA [ 6 ], and PISA, PISA/PESA was also calculated from the recorded data.…”
Section: Methodsmentioning
confidence: 99%
“…Periodontal examinations were performed to record tooth mobility, PD, BOP [ 21 ], and plaque control records [ 22 ]. The measurements were performed as previously described [ 23 ]. The lifestyle questionnaire was administered during the patients’ most recent session of periodontal therapy (SPT2).…”
Section: Methodsmentioning
confidence: 99%